2021
DOI: 10.1101/2021.08.02.454807
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Taxonomy of Rhizobiaceae revisited: proposal of a new framework for genus delimitation

Abstract: The alphaproteobacterial family Rhizobiaceae is highly diverse, with 168 species with validly published names classified into 17 genera with validly published names. Most named genera in this family are delineated based on genomic relatedness and phylogenetic relationships, but some historically named genera show inconsistent distribution and phylogenetic breadth. Most problematic is Rhizobium, which is notorious for being highly paraphyletic, as most newly described species in the family being assigned to thi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…However, in our study both the MLSA and WGS phylogeny and ANIb analysis showed that A. albertimagni AOL51 T is more closely related to Allorhizobium , suggesting that “ R. aggregatum complex” is not the best choice. This is in agreement with Kuzmanovic et al [55], who proposed the name “ Peteryoungia ” for strains formerly identified as “ R. aggregatum complex”, and also included A. albertimagni AOL51 T .…”
Section: Discussionsupporting
confidence: 91%
“…However, in our study both the MLSA and WGS phylogeny and ANIb analysis showed that A. albertimagni AOL51 T is more closely related to Allorhizobium , suggesting that “ R. aggregatum complex” is not the best choice. This is in agreement with Kuzmanovic et al [55], who proposed the name “ Peteryoungia ” for strains formerly identified as “ R. aggregatum complex”, and also included A. albertimagni AOL51 T .…”
Section: Discussionsupporting
confidence: 91%
“…The cpAAI between the isolate TH2 and reference Rhizobiaceae spp. were <76 % (Table S4), which was below the threshold of ∼86 % for delimitation of Rhizobiaceae genera proposed recently [60]. This suggested that isolate TH2 represents a new genus and species, described here as Onobrychidicola muellerharveyae gen. nov sp.…”
Section: Resultsmentioning
confidence: 57%
“…Branch supports were estimated with 200 Felsenstein bootstrap trees. The 16S tree was rooted using R. leguminosarum USDA 2370 T sequence, whereas the gyrB and MLSA trees were rooted using the sequence from “ A. albertimagni ” AOL15 – a distant relative incorrectly classified in the Agrobacterium genus for which a classification in the newly proposed genus “ Peteryoungia ” was proposed ( Kuzmanović et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%